Growth and characterization of La5/8Ca3/8MnO3 films by pulsed laser deposition on silicon wafer substrate - Navaseri, M.; Shaari, Abdul Halim; Lim, Kean Pah; Chen, Soo Kien; Abd Shukor, Roslan (Malaysian Solid State Science and Technology Society, 2014)
By pulsed laser ablation magnetoresistive perovskite-like La5/8Ca3/8MnO3 films have been successfully grown on silicon wafer substrates without any buffer layer. The X-ray diffraction (XRD) patterns of the LCMO/Si heterostructure indicate that well crystalline LCMO grows polycrystalline with average grain size of 15nm. The LCMO films exhibited typical characteristics of CMR material with the metal-insulator transition temperature at TP=245 K. The film has a maximum %MR of about %16.52 and mean surface roughness of about 147.4 nm.